Answer: k = 6+10x
=======================================================
Work Shown:
![64*4^(5x)\\\\\left(2^6\right)*\left(2^(2)\right)^(5x)\\\\\left(2^6\right)*\left(2^(2*5x)\right)\\\\\left(2^6\right)*\left(2^(10x)\right)\\\\2^(6+10x)\\\\](https://img.qammunity.org/2023/formulas/mathematics/high-school/bedyr02wlt4spe3y6lt4ah3tuddo8rlzf7.png)
The result is in the form
with k = 6+10x
------------------------
Step-by-step explanation:
First we need to get everything as an exponential expression with a base 2.
We rewrite 64 as
and 4 as
in the second step.
In the third step, I used the rule
which says to multiply the exponents together. That's how I went from
to
. Then the 2*5x in the exponent becomes 10x.
To wrap things up, I used the rule
which says to add the exponents when we multiply stuff of the same base together.